Bioprospecting red seaweed Palmaria palmata as source of bioactive lipids - Barbosa, Beatriz Fabiana Rodrigues (2023)
Palmaria palmata is an edible red seaweed rich in the omega-3 eicosapentaenoic acid (EPA), mostly esterified with polar lipids (phospholipids and glycolipids). EPA is known for its positive effects in health, namely in the prevention of non-communicable diseases. However, the polar lipid content of P. palmata is still undervalued and poorly explored. Therefore, this work aimed to (a) bioprospect the polar lipids from P. palmata as a source of add-value compounds with potential health benefits, focusing on their anti-inflammatory and antioxidant properties, and (b) correlate the bioactive potential with the lipid composition, through an untargeted lipidomic approach, using HILIC-ESI-MS/MS to identify and characterize the polar lipid profile. The total lipid extract as well as the glycolipid- and phospholipid-enriched extracts were shown to be sources of compounds with antioxidant potential, scavenging the radicals ABTS●+ and DPPH● in chemico, and reducing the intracellular oxidative stress in vitro, in RAW macrophages treated with lipopolysaccharide (LPS). The lipid extracts also showed an anti-inflammatory potential, inhibiting the COX-2 activity in chemico, and reducing the production of nitric oxide in vitro and the transcription of pro-inflammatory genes such as Nos2, IL1b, IL6, Tnf e Ptgs2, triggered by LPS in RAW macrophages. These results show that both the phospholipid- and glycolipid-enriched extracts seem to have a relevant role in the bioactivities demonstrated by the total lipid extract. The characterization of the lipid extracts by HILIC-ESI-MS/MS highlighted that the biomass of the seaweed P. palmata farmed in an integrated multitrophic aquaculture (IMTA) is a source of compounds with high nutritional value – namely omega-3 PUFAs – and bioactive compounds, mainly EPA-rich polar lipids, thus contributing to its valorisation as a healthy and functional food. Future studies are necessary to evaluate the bioaccessibility and bioavailability of these bioactive lipids, in order to ensure that the properties observed in chemico and in vitro will show in their in vivo utilization.